Degradation of PFOS by a MnO2/H2O2 process. Issue 12 (13th November 2020) - Chang, Yueh; Cho, Yi-Chin; Lin, Yi-Pin
Abstract : Degradation of PFOS by MnO2 /H2 O2 was systematically investigated and the role of reactive radicals on intermediate formation was characterized. Abstract : Perfluorooctanesulfonic acid (PFOS) has been used in various industries due to its excellent surfactant property and oxidative resistance. However, toxicology studies have shown that PFOS can cause adverse effects on ecological and human health. This study investigated the use of a MnO2 /H2 O2 process to generate reactive radicals for PFOS removal. Our results indicated that among the three MnO2 polymorphs (α-, β-, and γ-MnO2 ), γ-MnO2 was more effective in catalyzing H2 O2 to remove PFOS. 0.25 μM PFOS could be completely degraded in 15 min under the optimal conditions ([H2 O2 ] = 1 M, [γ-MnO2 ] = 20 mg L −1, initial pH = 7). Electron paramagnetic resonance (EPR) verified the formation of hydroxyl radicals (OH˙) and superoxide radicals (O2 ˙ − ) and X-ray photoelectron spectroscopy (XPS) revealed the evolutions of the Mn oxidation state and O coordination environment on the MnO2 surfaces in this process. Radical quenching experiments and intermediate identification indicated that the degradation of PFOS was initiated by the cleavage of the C–S bond, followed by that of the C–C bond and the C–F bond, leading to the formation of short-chain and defluorinated intermediates. Long-chain by-products were also identified, likely due to the recombination of organic radicals.